1997
DOI: 10.1063/1.365263
|View full text |Cite
|
Sign up to set email alerts
|

Stability of sulfur-treated InP surface studied by photoluminescence and x-ray photoelectron spectroscopy

Abstract: The degradation behavior of the sulfur-treated InP surface at relatively low temperature has been investigated with x-ray photoelectron and photoluminescence (PL) spectroscopy. The results showed that the treated surfaces were oxidized to In2O3, InPO3, and InPO4 at 250 °C and in a vacuum of 10−3 Torr for 20 min. As the holding time for S-treated InP under a vacuum of 10−3 Torr increased, the PL peak caused by the band edge transition decreased without the formation of oxides. It was therefore suggested that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 35 publications
(45 reference statements)
3
7
0
Order By: Relevance
“…The surface passivation of semiconductors, such as gallium arsenide (GaAs) and indium phosphide (InP), is of great significance to the performance characteristics of optoelectronic and photovoltaic devices, and other devices. The control of surface electronic characteristics and reactivity is also important for fundamental studies of electron transfer at the solid−liquid interface and photocatalysis. For InP, a few studies have reported on the chemical modification of the surface with thiol compounds, such as hydrogen sulfide H 2 S, , ammonium sulfide (NH 4 ) 2 S, and alkanethiols C n H 2 n +1 SH. , An alternative approach to the modification of oxidized InP surfaces (via an OH functionality) was presented by Sturzenegger and Lewis the formation of a SAM of alkanethiols on InP has not yet been fully characterized. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The surface passivation of semiconductors, such as gallium arsenide (GaAs) and indium phosphide (InP), is of great significance to the performance characteristics of optoelectronic and photovoltaic devices, and other devices. The control of surface electronic characteristics and reactivity is also important for fundamental studies of electron transfer at the solid−liquid interface and photocatalysis. For InP, a few studies have reported on the chemical modification of the surface with thiol compounds, such as hydrogen sulfide H 2 S, , ammonium sulfide (NH 4 ) 2 S, and alkanethiols C n H 2 n +1 SH. , An alternative approach to the modification of oxidized InP surfaces (via an OH functionality) was presented by Sturzenegger and Lewis the formation of a SAM of alkanethiols on InP has not yet been fully characterized. ,, …”
Section: Introductionmentioning
confidence: 99%
“…According to the In 3d 5/2 spectra represented in Fig. 3(a)–(c), all the samples were dominated by In–O bonds (some of the features of the In–O bond peak probably overlap with the In–S bond peak due to their similar binding energies 8), which may exist mainly in the form of In 2 O 3 at the interface region, even though a clear physical detection of this layer was not available via HRTEM analysis. Accompanying the gradual In 2 O 3 formation, the intensities of other features corresponding to various InP x O y states [probably In(PO 3 ) 3 and InPO 4 ] were also augmented as the deposition temperature was increased and, in particular, a substantial increase was evident at a deposition temperature of 300 °C, which corresponds well to the observed IL thickening described above.…”
mentioning
confidence: 99%
“…The precursor‐activated self‐cleaning is well known to become stronger as the deposition temperature increases during the ALD HfO 2 process on GaAs 5, which is contradictory to the current observation. Meanwhile, it is known that InP can be easily oxidized under a similar vacuum condition to the ALD process at a relatively lower temperature (270 °C) 8 than that of the ALD temperature, showing a substantial IL growth (300 °C). Considering these aspects, the observed insufficient IL removal during the early stage of the ALD HfO 2 growth at the highest temperature of 300 °C suggests a possible occurrence of temperature‐dependent oxidation of the InP substrate due to the strongly oxidizing environment, in parallel with the ALD‐induced self‐cleaning.…”
mentioning
confidence: 99%
“…The temperature dependence of dielectric properties was recorded by a HP 4284A impedance analyzer at the frequency of 1, 10, and 100 kHz in the temperature range from room temperature to 300°C with a heating rate of 3°C/min. 36 The formation of In 2 O 3Àx is induced by the increase in oxygen vacancy due to the oxygen loss at high temperature, among which x is to be determined. Strain versus electric field measurement was implemented with an optical probe system of MTI-2000 photonic sensor and a power system amplified by Trek 610D.…”
Section: (3) Annealing Treatment and Characterizationmentioning
confidence: 99%
“…3(a), which are tentatively attributed to In 2 O 3 (18.2 eV) and In 2 O 3Àx (17.6 eV) contributions. 36 The formation of In 2 O 3Àx is induced by the increase in oxygen vacancy due to the oxygen loss at high temperature, among which x is to be determined. In Fig.…”
Section: (3) Annealing Treatment and Characterizationmentioning
confidence: 99%